Simulation and experimental study on energy absorption components of advanced hydraulic support for mining - Xiaochun XIAO; Ziyang LI; Xin DING; Jun XU; Heng ZHU; Zhen DING (Meitan kexue jishu)
In order to improve the energy absorption performance of hydraulic support and solve the problems such as cylinder explosion of support column when roadway rock burst occurs, a kind of multi-cell tube energy absorption component with square tube and round tube nested with each other is proposed and applied in series to the hydraulic support. Based on the simplified super folding element theory, the energy dissipation path of multi-cell tubes is analyzed, and the equivalent axial load prediction formula of multi-cell tubes with different section shapes is derived. The energy absorption performance and buckling deformation morphology of multi-cell tubes with different section shapes under axial crushing were obtained by numerical simulation. It was found that multi-cell square tubes (SS type) had relative energy absorption advantages, and the reliability of numerical simulation was verified by experiments. Meanwhile, the average load obtained by numerical simulation and experiment was compared with the equivalent axial load predicted by theory. It is proved that the equivalent axial load prediction formula has high prediction accuracy. Based on the research foundation of aluminum foam filling method in multi-cell square tube, the filling method with 25% filling rate with relative energy absorption advantage was selected to carry out axial quasi-static compression test of aluminum foam filling multi-cell square tube with different porosity. The results show that the aluminum foam filling can improve the deformation resistance of the multicellular square tube. Among them, the load fluctuation of the multi-cell square tube with 71.18% porosity is the smallest, the effective deformation length and energy absorption are the largest, and the energy absorption effect is the best, which can make the energy absorption and displacement process more stable. When the impact velocity remains unchanged, under different impact energy conditions, compared with the with the traditional hydraulic support without adding energy absorbing components, the plastic energy of the support part is reduced by about 87%, the impact time is extended by about 307%, and the yield distance is increased by about 282%. The plastic deformation of the support is effectively reduced through the buckling deformation of the energy absorption component. Sufficient time is provided for the opening of the support column safety valve. The application of aluminum foam filled multi-cell square tube reduces the risk of cylinder explosion of the support column and improves the impact resistance of the column.